Topographic representation of auditory space in the superior colliculus of adult ferrets after monaural deafening in infancy. - King, A; Moore, DR; Hutchings, M (1994)
1. We have investigated the role of monaural cues provided by the outer ear in the construction of a map of auditory space in the superior colliculus. Single-unit recordings were made from the superior colliculus of adult ferrets that were deprived of binaural inputs by surgically ablating the ipsilateral cochlea on postnatal day 21 or 24. 2. The spatial response properties of auditory units in the deeper layers of this nucleus were studied using white-noise bursts presented under free-field conditions in an anechoic chamber. The thresholds of the units recorded in the monaural ferrets were not significantly different from those recorded in the superior colliculus of normal adult ferrets. In both groups the unit thresholds varied by 30-50 dB in each region of the superior colliculus. 3. In normal and monaural ferrets the elevation tuning tended to be sharper than the azimuth tuning. At sound levels of approximately 10 dB above threshold the auditory units recorded in both groups of animals were tuned to a specific region of space that was restricted in azimuth and elevation. The spatial location at which the maximum response was obtained (auditory best position) varied topographically in azimuth along the rostrocaudal axis of the nucleus and in elevation along the mediolateral axis. 4. The azimuthal distribution of best positions associated with each recording location in the superior colliculus of the monaural ferrets and the alignment between this dimension of the auditory map and that of the visual map in the overlying superficial layers were no different from those found at corresponding near-threshold sound levels in normal ferrets. 5. Elevation spatial selectivity was examined in a smaller sample of units. Although elevation best positions shifted downward from the medial to the lateral side of the nucleus in both normal and monaural ferrets, we found that the topography of the auditory representation and its alignment with the visual representation were statistically different in the two groups of animals. 6. Increasing the sound level does not affect the representation of auditory space in normal ferrets. However, when the stimulus level presented to monoaural ferrets was increased, the receptive fields either expanded so that the responses were no longer tuned to any particular region of space, or the responses remained tuned but exhibited a marked shift in the value of the best position.(ABSTRACT TRUNCATED AT 400 WORDS)